On some interesting Orthoptera: Tettigoniidae and Acrididae from tropical Africa - Massa, Bruno (Zootaxa, 2022)
The author reports the results of the study of specimens of Orthoptera collected in Côte d’Ivoire, Sierra Leone and Kenya; two new species are described: Eulioptera bartolozzii n. sp. from Kenya, and Mangomaloba excavata n. sp. from Sierra Leone. Mangomaloba latipennis Chopard, 1954 from Guinea is synonymized with Morgenia rubricornis Sjöstedt, 1913 from Democratic Republic of the Congo, Central African Republic, Gabon and Côte d’Ivoire. Further, new distributional data of other five species are reported.